Hospitality Strategic Management Planning Post COVID-19 Pandemic: A Study from Local Hotel Chain - Maemunah, Ita; Wijaya, Naufal; Sukmadi (Politeknik Pariwisata NHI Bandung, 2023)
Purpose of the study: This study aims to analyze management planning and strategies implemented by local chain hotels post-COVID-19 pandemic. Design/methodology: This study uses a descriptive qualitative case study method, with two research instruments in data collection: documentation and interviews. Data reduction, data presentation, and data verification, as well as SWOT analysis, were used to analyze data. Regarding testing validity data, the technique used by researchers is a triangulation technique source. Findings: The Local chain hotel has implemented a competitive strategy well, proven with properties that can last for more than 28 years in the hospitality industry, and is still relevant in the competition between hotels today. Management can also maintain hotel operations during the COVID-19 pandemic without closing all their properties. Research limitations/Implications: This study only focuses on using a SWOT analysis tool to analyze the Hotel's internal and external environment, where many tools could be used in data analysis to produce more reliable output. Novelty/Originality of the study: This study discussed formulation local chain hotels strategy formulation post-COVID-19 pandemic. The formulation covering four pillars of the hospitality industry, including operational, marketing, finance, and human resources. This research can be a reference for local hotels in implementing competitive strategies.